2020
DOI: 10.1002/vms3.386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various levels of sweet almond meal as a source of protein on the production variables and immune response of broiler chickens

Abstract: This study was conducted to evaluate effects of a sweet almond meal (SAM) as a source of protein on performance and immune responses of broiler chickens. Treatments consisted of different levels of SAM (7%, 14%, 21% and 28% of diet) and control diet that was performed in a completely randomized design in 42 days. Body weight gain (BWG) and feed intake (FI) were recorded weekly. Carcass characteristics and blood variables were measured on the 42 day of age. Immune response to sheep red blood cell (SRBC) was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The production performance of broilers was significantly improved when perilla seed meal replaces 1-2% soybean meal in the diet [22]. In addition, substituting soybean meal in the diet with plant protein raw materials like fermented rapeseed meal, raw chickpea, sweet almond meal, raw and fermented rapeseed cake, and sprouted whole pearl millet can also contribute to maintaining or even enhancing the growth and development of broilers [23][24][25][26][27]. In the experiment, the substitution of 5-10% soybean meal with ZBM significantly improved the ADG and ADFI of broilers, which supports the feasibility of using ZBM in broiler diets.…”
Section: Discussionmentioning
confidence: 99%
“…The production performance of broilers was significantly improved when perilla seed meal replaces 1-2% soybean meal in the diet [22]. In addition, substituting soybean meal in the diet with plant protein raw materials like fermented rapeseed meal, raw chickpea, sweet almond meal, raw and fermented rapeseed cake, and sprouted whole pearl millet can also contribute to maintaining or even enhancing the growth and development of broilers [23][24][25][26][27]. In the experiment, the substitution of 5-10% soybean meal with ZBM significantly improved the ADG and ADFI of broilers, which supports the feasibility of using ZBM in broiler diets.…”
Section: Discussionmentioning
confidence: 99%
“…Almonds increase high-density lipoprotein (HDL) cholesterol and reduce low-density lipoprotein (LDL) cholesterol levels in humans when included in the diet [ 41 ]. A previous study reported that including almonds in the diet reduced plasma cholesterol, triglycerides (TG), and LDL cholesterol levels, and increased HDL cholesterol levels in broilers [ 42 ]. Similarly, Arjomandi et al [ 43 ] found that blood cholesterol levels in quails fed diets containing 20% and 30% almonds were significantly lower than those of quails fed diets containing 10% almonds and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Almond tree (Prunus dulcis) is cultivated all over the world and mostly in the United States and Mediterranean countries. The worldwide almond fruit production is estimated at about three million tonnes per year with a very rapid growth rate in recent years (about 5% annually) (Moradi Yeganeh et al 2021).…”
Section: Introductionmentioning
confidence: 99%